Diagnóstico participativo de salud en usuarios de un programa de hipertensión arterial (2006)
ABSTRACT: This article displays the results of an investigation about a popular District Health Program in Medellin carried in 2003. Objective: To obtain knowledge of protective processes and deteriorating determinants in the health conditions of 160 users of the program Methodology and materials: The study is descriptive cross-sectional. It integrates some qualitative and quantitative techniques to explore the conditions of health and the perceptions that users and community actors have in relation to hypertension. Theoretical-methodological elements of critical epidemiology and epidemiological monitoring were applied. Results, discussion: The influence of the socioeconomic and political context in the process health-disease process and the negative impact of the health reform in the prevention programs are stressed. It highlights the valuation of the users regarding the suburban attention centers and the program as encounter and refuge scenario against solitude and paint, the deficiencies of the social support networks and the weak familiar support in the care of the patients. Conclusions: 83% of the users are women of the third age, their majority (85%) belongs to the low layer, but (50%) of them were not tied to any Health Regime. That explains the destructive processes of their health which should be intervened by epidemiological monitoring.